The relationship between work-life balance, stress and job performance among housemen in The Ministry of Health, Malaysia - Muhammad Radzi, Rusnida; Musa, Siti Nur Syuhada; Hamzah, Siti Raba’ah (Human Resource Management Academic Research Society, 2022)
Work life balance is one of the main factors that influence the individual job performance. Understanding the criticality of work-life balance and stress is important because these factors contribute to Housemen's job performance throughout housemanship in training hospitals. Therefore, the objectives of this study were to examine the relationship between work-life balance, stress and job performance among Housemen as well as to determine the predictors of work-life balance and stress toward job performance among Housemen in the Ministry of Health (MOH). This study involved a total of 150 Housemen who were practicing housemanship in MOH hospitals for at least one year. A quantitative approach was used, and a set of self-administered reported structured questionnaires was used for data collection. The data was analyzed by SPSS software version 26.0 using the Pearson correlation and multiple linear regression. The findings indicated that there was a significant relationship between work-life balance, stress and job performance among Housemen in MOH. Work-life balance was found to be a significant predictor of job performance among Housemen. The findings also provided insights for hospital management to review current approaches and work schedules, supervision, evaluation, and welfare of Housemen.